FAKTOR-FAKTOR YANG MEMPENGARUHIKURS RUPIAH TERHADAP YEN TAHUN 1970 - 2002: ERROR CORRECTION MODEL (ECM) - Karunia, Nurul Yuniataqwa; Cahyadin, Malik (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
This research aims to find out factors influencing the exchange rate of rupiah toward yen. The approach used to analyze time series data in this study is monetary approach with ECM as the chosen regression model. The year of observation was begun in 1970-2002. Based on regression which done, the result showed that there is the significant correlation between independent variable (MI,Yreal, NP1) with dependent variable (exchange rate of Rupiah fYen). The correlation happens either in long or short term.